USING ELEMENTS OF MATHEMATICAL ANALYSIS IN SOLVING TRIGONOMETRIC EQUATIONS - Turg‘inov A (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the use of elements of mathematical analysis in solving trigonometric equations.